A Comparative Study of Investigation of Advanced Materials ‎for Shipbuilding - Chidambaram, K.R.; Rajan , P. (International Journal of Basic and Applied Sciences, 2025)
It is, in fact, a traditional mode of transportation and cargo above the sea that humans have used since ancient times to travel across water ‎bodies. Super carriers, which are used for aircraft carriers weighing more than 70,000 tons, are currently the most prevalent type of navy ‎ship. Planes are transported by aircraft carriers. Battleships are larger than cruisers and destroyers and are equipped with superior ‎armaments. Helicopter carriers are warships that transport aircraft. Cruisers are massive warships designed for long, fast cruises. During ‎assaults, larger warships are accompanied by destroyers. One kind of escort transportation is a frigate. Cor Shipping was regarded as one of ‎the most secure and cost-effective ways to move people and products. Since ancient times, the shipbuilding industry has been a significant ‎and prosperous business. The majority of the activity in the shipbuilding industry were concentrated in the shipbuilding and ship repair ‎sectors amongst them Organizations, including those in the shipbuilding industry, relied heavily on human resource development (HRD). ‎HRD was no longer a support department in today's world; rather, it played a crucial role in businesses. Therefore, recruiting, training, ‎nurturing, and retaining human capital were some of the most important aspects in any organization. The shipbuilding sector in India ‎included ship builders, ship repairers, seafarers, regulators, administrators, insurers, surveyors, equipment manufacturers, port & terminal ‎operators, coast guard, navy, and training establishments. Human resource management, once regarded as one of the most important tools ‎for an organization's growth and development, faced a paradox in this industry today. The industry was at a crossroads between strategies ‎for development and expansion and attracting, training, and retaining human resources for the industry, which has now become quite a ‎challenge‎.
Keywords: Shipbuilding; Advanced Materials; Comparative Study